Spatial analysis of magnetic resonance T1ρ and T2 relaxation times improves classification between subjects with and without osteoarthritis - Carballido‐Gamio, Julio; Stahl, Robert; Blumenkrantz, Gabrielle; Romero, Adan; Majumdar, Sharmila; Link, Thomas M. (Medical physics (Lancaster), 2009)
Purpose: Studies have shown that functional analysis of knee cartilage based on magnetic resonance (MR) relaxation times is a valuable tool in the understanding of osteoarthritis (OA). In this work, the regional spatial distribution of knee cartilageT1ρ and T2 relaxation times based on texture and laminar analyses was studied to investigate if they provide additional insight compared to global mean values in the study of OA. Methods: Knee cartilage of 36 subjects, 19 healthy controls and 17 with mild OA, was divided into 16 compartments.T1ρ and T2 relaxation times were studied with first order statistics, eight texture parameters with four different orientations using gray‐level co‐occurrence matrices and by subdividing each compartment into two different layers: Deep and superficial. Receiver operating characteristic curve analysis was performed to evaluate the potential of each technique to correctly classify the populations. Results: Although the deep and superficial cartilage layers had in general significantly differentT1ρ and T2 relaxation times, they performed similarly in terms of subject discrimination. The subdivision of lateral and medial femoral compartments into weight‐bearing and non‐weight‐bearing regions did not improve discrimination. Also it was found that the most sensitive region was the patella and that T1ρ discriminated better than T2. The most important finding was that with respect to global mean values, laminar and texture analyses improved subject discrimination. Conclusions: Results of this study suggest that spatially assessing MR images of the knee cartilage relaxation times using laminar and texture analyses could lead to better and probably earlier identification of cartilage matrix abnormalities in subjects with OA.